Rhythms of the Kimberley a seasonal journey through Australia's north - Gueho, Russell (Russell Philip) (Fremantle Press, 2007)
"A natural history of the Kimberley Region, Western Australia. It is intended to remind people about the cyclical nature of the world around us and the importance for us to re-acquaint ourselves with the seasonal indicators that effectively dominate our lives in some way or another."--Provided by publisher.